Synergistic electromagnetic wave absorbing properties of NiFe2O4/MWCNT composites synthesized via microwave-assisted combustion method in Ku-band - Johari, Mohd Hilmi; Ismail, Ismayadi; Azis, Rabaah Syahidah; Chan, Kar Tim; Mohamed Nafis, Nur Biha; Ertugrul, Mehmet; Karakaş, Ibrahim Hakki (Universiti Malaysia Perlis, 2025)
This study investigates the synthesis, microstructural characteristics, magnetic properties, and electromagnetic wave absorption performance of nickel ferrite (NiFe2O4) composites reinforced with multi-walled carbon nanotubes (MWCNTs) synthesized via the microwave-assisted combustion (MAC) method. X-ray diffraction (XRD) analysis confirmed the desired structure of NiFe2O4 and the successful integration of MWCNTs within the NiFe2O4 matrix. Field emission scanning electron microscopy (FESEM) analysis revealed the entanglement of MWCNTs and their significant impact on hindering particle growth, resulting in a finer particle structure. The reduction in average particle size from 1.317 µm for pure NiFe2O4 to 0.436 µm for NiFe2O4 with 2wt% MWCNT, representing approximately a 66.89% reduction, significantly demonstrates the effectiveness of MWCNTs in limiting particle growth and promoting a more refined particle structure. Magnetic property analyses showed a nuanced interplay between MWCNT concentration and composite behaviour, with the saturation magnetization (Ms) exhibiting substantial enhancement in the NiFe2O4/2wt%MWCNT composite, indicative of effective alignment of magnetic moments. However, a subsequent decrease in Ms at higher MWCNT concentrations (4wt% and 6wt%) suggested potential dilution effects and disruptions in magnetic interactions within the composite. Electromagnetic wave absorption investigations revealed NiFe2O4/4wt%MWCNT as a highly efficient absorber in the Ku-band, with superior impedance matching and a high attenuation constant. The reflection loss (RL) reached a maximum of –17.58 dB at 12.78 GHz, signifying absorption of more than 99% of the incident EM wave in the microwave range. The favourable impedance matching and high attenuation constant contributed to the superior performance of NiFe2O4/4wt%MWCNT compared to pure NiFe2O4 and MWCNT. These findings suggest the potential of NiFe2O4/MWCNT composites for applications in telecommunications, aerospace, and electronics, with opportunities for further optimization and investigation into long-term stability and durability under varying environmental conditions.